An S matrix analysis of the Z resonance - Dova, María Teresa (1993)
The S matrix ansatz is a rigorously model independent approach to describe the cross-sections and asymmetries in e+e- annihilation. Using the cross-sections and asymmetries measured with the L3 detector during the 1990 and 1991 running period, we determine the mass and the width of the Z boson, the contributions of the Z exchange and of the yZ interference. Including the polarization of the t lepton in the analysis, the leptonic helicity amplitudes of the scattering process are determined assuming lepton universality. The results are compared with other model independent ansatzes as realized in ZFITTER. A systematic bias of the Z mass due to the yZ interference term is detected, which leads to an underestimation of the error on mz for model independent determinations.